2020
DOI: 10.1021/acs.jced.9b01110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemically Activated Microsized Zero-Valent Iron/Pyrite Composite for Effective Hexavalent Chromium Sequestration in Aqueous Solution

Abstract: The activity of pyrite (FeS2) and microsized zero-valent iron (mZVI) is greatly limited by the passivating layer. This study indicated that hexavalent chromium (Cr­(VI)) could be effectively sequestered by mechanochemically activated mZVI/FeS2 composite (MA-mZVI/FeS2), which was obtained from the mZVI/FeS2 mixture by mechanochemical technology. Compared with MA-mZVI and MA-FeS2, the Cr­(VI) removal performance of MA-mZVI/FeS2 was significantly improved at a mZVI/FeS2 molar ratio of 1:9. The effects of initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…A simple physical coating of FeS x on the ZVI surface could result in discontinuity across the two domains despite the fairly good conductivity they both possess. 11,12 To resolve this issue, one should ensure that the electrons can efficiently pass through the cross section. Chemical bonds could be a bridge to foster electron transport between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…A simple physical coating of FeS x on the ZVI surface could result in discontinuity across the two domains despite the fairly good conductivity they both possess. 11,12 To resolve this issue, one should ensure that the electrons can efficiently pass through the cross section. Chemical bonds could be a bridge to foster electron transport between the two phases.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the ecologically friendly alternative adsorbent created from CF-AC can be employed effectively to remove Cr and Pb(II) ions from tannery wastewater. ZVI was found to be excellent at removing pollutants from wastewater, such as toxic metal ions (Ullah et al, 2020., He et al, 2020). Extensive research work was conducted on removing Wastewater Treatment Using Activated Carbon Produced from Oil Shale metals from wastewater using ZVI stabilized on carbon material, (Qu et al, 2017;Zhou et al, 2014;Congbin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cr (VI) is highly water soluble and toxic than Cr (III). [11] The maximum permissible limit for Cr (VI) in water is 0.1, 0.05 and 0.01 mg/L has been recommended by the World Health Organization (WHO), US Environmental Protection Agency (USEPA), and the Central Pollution Control Board (CPCB) India, respectively. [12,13] Long-term exposure to hexavalent chromium more than the permissible limit can cause nausea, nervous disorder, kidney failure, liver diseases, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Chromium exists in water as hexavalent chromium (Cr (VI)) and trivalent chromium (Cr (III)). Cr (VI) is highly water soluble and toxic than Cr (III) [11] . The maximum permissible limit for Cr (VI) in water is 0.1, 0.05 and 0.01 mg/L has been recommended by the World Health Organization (WHO), US Environmental Protection Agency (USEPA), and the Central Pollution Control Board (CPCB) India, respectively [12,13] .…”
Section: Introductionmentioning
confidence: 99%